Effect of Oral Administration with Lactobacillus plantarum CAM6 Strain on Sows during Gestation-Lactation and the Derived Impact on Their Progeny Performance - César Betancur; Yordan Martínez; Guillermo Tellez-Isaias; Rogel Castillo; Xinghua Ding (Hindawi Limited, 2021)
Background. To evaluate the biological response of the sows and their offspring with oral administration of Lactobacillus plantarum CAM6 in breeding sows, a total of 20 Pietrain breeding sows with three farrowings and their descendants were used, randomly divided into two groups of 10 sows each. Treatments included a basal diet (T0) and basal diet +10 mL biological agent containing 109 CFU/mL L. plantarum CAM6 (T1). No antibiotics were used throughout the entire experimental process of this study. Results. The L. Plantarum CAM6 supplementation in sows' feeding did not affect (P>0.05) the reproductive performance of the sows; however, the number of deaths for their offspring before weaning (P≤0.05) decreased. In addition, the oral administration of Lactobacillus plantarum CAM6 in sows increased (P≤0.05) the content of lactose, nonfat solids, mineral salts, and the density of sows' milk, with a decrease in milk fat. Moreover, the probiotic feed orally to the sows improved the body weight (P≤0.05) and reduced the diarrhea incidence of their offspring (P≤0.05). Also, the probiotic administration of sows changed (P≤0.05) the serum concentration of Na+, pCO2, and D-β-hydroxybutyrate and increased (P≤0.05) the leukocytes, lymphocytes, and platelets in their piglets. Conclusion. Oral administration of Lactobacillus plantarum CAM6 in breeding sows improved body weight, physiological status, and the health of their offspring. And preparing the neonatal piglets physiologically is of great importance to the pig farming industry which could decrease the operational cost and medication (especially antibiotics) consumption of the pig producers.